Issues in the Creation of Organizations: Initiation, Innovation, and Institutionalization - Kimberly, John R. (Academy of Management Journal, 1979)
This paper summarizes some of the most important findings of a longitudinal study of the birth and early development of an innovative organization. Paradoxically, those features of the organization that led to its success as an innovation in the short run were incompatible with requirements for survival in the longer run. These findings underscore the advantages of a biographical approach to organizational analysis.